Atractividad de la literatura de César Vallejo para la diversificación de la oferta turística primordial de la provincia de Santiago de Chuco en la región La Libertad. - Tamashiro Cenas, Yoshi Luis (2018)
The purpose of this report is to determine the attractiveness of César Vallejo's literature for the diversification of the primordial tourist offer of the province of Santiago de Chuco in the La Libertad region, that are manifested in intrinsic qualities (uniqueness and identity) and extrinsic qualities (expectations and preferences), analyzed from the poems "Los Heraldos Negros" and "Trilce", _x000D_ The intrinsic qualities are expressed in a varied literary production inspired by a natural and cultural landscape such as "the downpour" and "life in the countryside", domestic architectural elements such as the "poyo", and the popular Santiago de Chuco´s speech as the word "tahuashando"; and a community identified by keeping the poet in the urban environment, promoting a literary education from an early age and forming literary cultural associations. On the other hand, the extrinsic qualities of a real tourist with expectations and preferences motivated by knowing spaces associated with the author, by having their own adventurous version when entering geographical landscapes, by creating literature from their own inspiration or simply out of curiosity. _x000D_ Methods such as the Analytical- Synthetic and Ethnographic have been used with techniques such as Mapping, Interview, Observation and Survey, with which the natural and cultural landscape has been zoned, generating 10 maps made in Arcgis 2.0, managers, teachers and literary associations have been interviewed generating 10 hermeneutical units processed in Atlas ti., the tourism resources has been observed that evidenced in the literature developing 7 observation tables; and 105 tourists who visited the House Museum between July and November 2017 and 100 university students from the community of Santiago have been surveyed.